Efektivitas Curcuma Longa sebagai Herbal Preventif dalam Bidang Obstetri-Ginekologi, Pediatri, dan Patologi Anatomi : Kajian Sistematik - Fransiska Mochtar; Saddam Muhdi; Hengky Ardian; Siska Silviana (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Curcuma longa (turmeric) is a widely known herbal plant due to its active compound, curcumin, which possesses anti-inflammatory, antioxidant, and immunomodulatory properties. This review aims to evaluate the preventive effectiveness of Curcuma longa in the fields of obstetrics-gynecology (obgyn), pediatrics, and anatomical pathology. The review was conducted following the PRISMA 2020 guidelines. Literature was searched from PubMed, Scopus, Cochrane Library, and Google Scholar for studies published between 2015 and 2025. Keywords used included: "Curcuma longa", "curcumin", "prevention", "obstetrics", "gynecology", "pediatrics", "anatomic pathology", and "herbal medicine". Articles were selected based on inclusion criteria and evaluated for quality using the JBI Critical Appraisal Tool. Of the 785 articles found, 19 studies met the inclusion criteria. In the obgyn field, curcumin was effective in preventing preeclampsia and endometriosis through modulation of inflammation and angiogenesis. In pediatrics, curcumin showed protective effects against respiratory and gastrointestinal disorders. In anatomical pathology, curcumin was found to inhibit preneoplastic cell transformation and suppress early histopathological changes. Curcuma longa shows great potential as a preventive agent across various medical disciplines. However, further clinical trials with strong study designs are needed to support its application in routine clinical practice